PENGEMBANGAN MEDIA FLANEL PINTAR UNTUK MENGENALKAN ANGKA 1-10 PADA ANAK USIA 4-5 TAHUN - Umamah, Kholifatul; Nugrahani, Risma; Rahmah, Hany'atur (Program Studi PG PAUD Universitas PGRI Ronggolawe, 2024)
(This research was motivated by the lack of media availability to introduce numbers 1-10 to children aged 4-5 years. So the formulation of the problem in this study, namely the availability of media to introduce numbers is still lacking so that teachers still use books or ordinary blackboards that are still monotonous, so teachers are required to be more creative in making various learning media for children. This research was conducted with the aim of developing Smart Flannels as a medium to introduce numbers 1-10. in children aged 4-5 years and to determine the feasibility of Smart Flannel media to introduce numbers to children. This research is considered a type of development research or what is called Research and Development (R&D) according to Borg and Gall. processes that must be taken include: 1) Research and Data Collection, 2) Planning, 3) Product Design Development, 4) Initial Field Trials, 5) Revision of Trial Results, 6) Field Testing of Main Products, 7) Product Revisions, 8) Product Validation, 9) Final Product Revision, 10) Dissemination. This Smart Flannel Media was tested and validated by media experts and material experts. The data analysis technique carried out in this study used qualitative and quantitative data obtained from product quality assessments and qualitative data, namely from the scores obtained from questionnaires filled out by media and material experts. The results of the validation conducted by media experts in stage one with a validity percentage of 78.3% (Good / Feasible). In stage two, the percentage of validity is 83.3% (Very Good / Very feasible). Validation results by material experts at stage one get a validity percentage of 74.87% (Good / Feasible). in the second stage getting a validity percentage of 84% (Very Good / Very feasible). From the results above, after calculating the results of the validity percentage of 79.75% which can be categorized as Good / Eligible. From the results above, it can be concluded that Smart Flannel media deserves to be used as a medium for introducing numbers 1-10 to children aged 4-5i years.